Value of extranodal extension detected by computed tomography for predicting clinical response after chemoradiotherapy in head and neck squamous cell cancer. (3rd April 2018) - Moon, Hyun; Choi, Young Jun; Lee, Yoon Se; Lee, Sang Wook; Kim, Sung Bae; Roh, Jong-Lyel; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract: Objectives: Radiological extranodal extension (rENE) upon CT is obtained before concurrent chemoradiation therapy (CCRT) for head and neck squamous cell carcinoma (HNSCC). We evaluated the prognostic value of rENE, rather than pathologically proven ENE, in patients who received CCRT for HNSCC. Materials and methods: We reviewed 117 patients. We divided the patients into rENE(+) and rENE(−) groups and evaluated overall survival (OS) and disease-specific survival (DSS), and factors affecting these outcomes. Results: Median follow-up was 37.4 months; 31 patients (26.2%) died and 26 (22.2%) had recurrence. Thirty patients were rENE(+) and these had worse 5-year OS (74% vs. 94%, p  < .01) and DSS (42% vs. 84%, p  < .01) rates compared with the rENE(−) group ( n  = 87). rENE (hazard ratio [HR] 3.57, p  < .05) and complete response (HR 3.55, p  < .05) affected OS. Clinical T stage (HR 2.86, p  < .05), rENE (HR 2.88, p  < .05), and complete response (HR 7.03, p  < .01) affected DSS. rENE(+) increased risk of incomplete response (IR) compared with the rENE(−) group ( p  < .05). Conclusions: CT findings suggesting ENE predicts treatment response to CCRT and prognosis, and could be used to determine the treatment modality for HNSCC.